Activation of SARS-CoV-2 neutralizing antibody is slower than elevation of spike-specific IgG, IgM, and nucleocapsid-specific IgG antibodies - Takahashi, Maika; Ai, Tomohiko; Sinozuka, Konomi; Baba, Yuna; Igawa, Gene; Nojiri, Shuko; Yamamoto, Takamasa; Yuri, Maiko; Takei, Satomi; Saito, Kaori; Horiuchi, Yuki; Kanno, Takayuki; et al. (Scientific reports, 2022)
COVID-19 antibody testing has been developed to investigate humoral immune response in SARS-CoV-2 infection. To assess the serological dynamics and neutralizing potency following SARS-CoV-2 infection, we investigated the neutralizing (NT) antibody, anti-spike, and anti-nucleocapsid antibodies responses using a total of 168 samples obtained from 68 SARS-CoV-2 infected patients. Antibodies were measured using an authentic virus neutralization assay, the high-throughput laboratory measurements of the Abbott Alinity quantitative anti-spike receptor-binding domain IgG (S-IgG), semiquantitative anti-spike IgM (S-IgM), and anti-nucleocapsid IgG (N-IgG) assays. The quantitative measurement of S-IgG antibodies was well correlated with the neutralizing activity detected by the neutralization assay (r = 0.8943, p < 0.0001). However, the kinetics of the SARS-CoV-2 NT antibody in severe cases were slower than that of anti-S and anti-N specific antibodies. These findings indicate a limitation of using the S-IgG antibody titer, detected by the chemiluminescent immunoassay, as a direct quantitative marker of neutralizing activity capacity. Antibody testing should be carefully interpreted when utilized as a marker for serological responses to facilitate diagnostic, therapeutic, and prophylactic interventions.